Analysis of fish farming business in floating cages in Jembayan Village, Kutai Kartanegara Regency - Pratama, Muhammad Yoga; Susilo , Heru; Darmansyah, Oon (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2024)
Cage cultivation is one of the cultivation techniques that is widely practiced by people who live around the river, because cage cultivation is easy and effective to do. The description of the people in Jembayan Village who have fish cultivation in cages is quite a lot and as a source of livelihood because the resulting production is very clear to meet the needs of the people in Jembayan Village. Based on this, this study aims to determine the amount of costs, profits and business feasibility with RCR and Payback Period criteria from fish farming in cages in Jembayan Village, Kutai Kartanegara Regency. The methods used in this research are simple random sampling, analysis of production costs and profits and analysis of business feasibility. The amount of costs used in the tilapia and goldfish cultivation business amounted to Rp143,442,967, - while the amount of revenue obtained by the cultivator was Rp 260,226,000, - Thus, the total profit obtained from all cultivators was Rp 116,783,033. The total R/C Ratio value of 2 and payback period of 3 means that every rupiah of total costs incurred for the tilapia aquaculture business will generate total revenue of Rp 2,000,000, - with a payback period of investment costs of 3 years or 36 months.